Apolipoprotein E-mediated Modulation of ADAM10 in Alzheimer's Disease - Shackleton, Ben; Crawford, Fiona; Bachmeier, Corbin (Current Alzheimer research, 2017)
The APOE4 allele is the strongest genetic risk factor for Alzheimer's disease (AD). It has been associated with an accumulation of amyloid-β (Aβ) in the brain, which is produced through the sequential cleavage of the amyloid-β precursor protein (AβPP) by β - and γ-secretases. Alternatively, AβPP is also cleaved by α -secretases such as A Disintegrin and Metalloproteinase Domain-containing Protein 10 (ADAM10). While several studies have investigated the impact of apoE on β- and γ-secretase, interactions between apoE and α-secretases have not been fully examined. We investigated the effect of each apoE isoform on ADAM10 in vitro and in human cortex samples. ADAM10 activity and kinetics was assessed in cell-free assays and the biological activity of ADAM10 further investigated in 7WCHO cells over-expressing wild type AβPP through ELISA. Finally, ADAM10 expression and activity was observed in the soluble fraction of both control and Alzheimer's Disease human cortex samples through ELISA. In a cell free assay, ADAM10 activity was found to be significantly lower in apoE4 samples compared to apoE2. 7WCHO cells over expressing wild type AβPP exposed to apoE4 demonstrated reduced formation of sAβPPα compared to other apoE isoforms. We also identified APOE and AD dependent changes in ADAM10 activity and expression in the soluble brain fraction of human brain cortex. Overall, our data demonstrates an apoE isoform-dependent effect on ADAM10 function and AβPP processing which may describe the elevated amyloid levels in the brains of AD subjects carrying the APOE4 allele.